Analysis and Visualization of Big data and Information Using Generative Artificial Intelligence Technology - Abdelmagid, Ahmed Sadek; Jabli, Naif Mohammed; Ibrahim, Asem Mohammed; Teleb, Ahmed Ali (International Journal of Innovative Research and Scientific Studies, 2025)
The current research aims to develop the skills of analysis and visual representation of big data and information through the use of generative artificial intelligence technology among graduate students in the course "Computers in Education." To achieve this goal, a quasi-experimental approach with a two-group design was used, and a random sample of graduate students at the College of Education, King Khalid University, was selected. The number of the experimental group was 32 students, and the number of the control group was 32 students. The experimental group was trained using the fourth version of generative artificial intelligence technology. A test was prepared for the skills of analyzing and representing data and information. The "t" test was also used, and the effect size was calculated to analyze the research results. The results indicated that the use of generative artificial intelligence technology, with its various platforms, has contributed significantly to the development of the skills of analysis and visual representation of big data and information.